Woman as a Subaltern in Canadian Literature - Bodal, Ewa (Romanica Silesiana)
The article takes as its subject the possibility of perceiving women as constituting a distinct subgroup of the subaltern. Following a theoretical introduction to this concept, the article focuses on the practical application of the notion in Canadian literature, discussing the two major female-authored Canadian novels published in the 1970s, that is Margaret Atwood’s Surfacing and Margaret Laurence’s The Diviners. Although Atwood’s and Laurence’s novels highlight the influences of the opposite colonial centres, the postcolonial situations and reflections of the main female characters appear quite similar. Indeed, both Atwood’s narrator and Laurence’s Morag Gunn seem to be depicted as doubly colonised: as women, and as Canadians. However, there exists a possibility of reading the protagonists as occasionally acting from a position of superiority towards those subaltern to them, namely the Native population. Key words: Canadian literature, feminism, postcolonialism, subalternity.